Birth of live llama (Lama glama) derived from embryo transfer storage at 5 °C for 24 h - Aller Atucha, Juan Florencio (2015)
The objective of the present work was to evaluate the efficacy of maintaining llama embryos metabolically inhibited but viable at 5 °C during 24 h. Adult females (n = 20) were used as embryo donors and were superstimulated with eCG. A total 61 embryos were non-surgically collected from 16 of the 20 llamas flushed at Day 7 after mating. Fourteen excellent hatched blastocysts were stored in sterile test tubes containing 1.5 ml of TCM 199-Hepes + 10% cow serum (v/v concentration) + antibiotics and cooled to 5 °C (cooling rate = 0.5 °C/min) and maintained at 5 °C during 24 h. After this, the embryos were warmed on warming plate (38 °C), washed three times and loaded individually into 0.25 ml French straws. Fourteen adult llamas were used as recipients and embryos were transferred only into the left uterine horn of the recipient regardless of side ovulation. All recipient llamas were pregnancy tested by transrectal ultrasonography at 45 days after transfer. Three (21.5%) pregnant females were detected and delivered three normal healthy male calves at term. To our knowledge, these offspring are the first llamas produced following transfer of refrigerated embryos. In summary, llama embryos can be cooled to 5 °C and maintained in storage for up to 24 h without significant losses of viability.